Collisions of chaotic attractors - Dellnitz, Michael (Schlaglichter der Forschung: Zum 75. Jahrestag der Universität Hamburg)

Improvements in beam search for 10000-word continuous-speech recognition - Haeb-Umbach, Reinhold; Ney, Hermann (IEEE Transactions on Speech and Audio Processing)
The authors describe the improvements in a time-synchronous beam search strategy for a 10000-word continuous-speech recognition task. Basically they introduced two measures, namely a tree organization of the pronunciation lexicon and a novel look-ahead technique at the phoneme level. The experimental tests performed showed that the number of state hypotheses could be reduced from 50000 to 3000, i.e., by a factor of about 17. At the same time, the word error rate did not increase.

Progress in Large-Vocabulary, Continuous Speech Recognition - Ney, Hermann; Steinbeiss, Volker; Aubert, Xavier L.; Haeb-Umbach, Reinhold (Artifical Intelligence, Progress and Prospects of Speech Research and Technology, Munich)

An Overview of the Philips Research System for Large Vocabulary Continuous Speech Recognition - Ney, Hermann; Steinbeiss, Volker; Haeb-Umbach, Reinhold; Tran, Bach Hiep (International Journal on Pattern Recognition and Artificial Intelligence)
This paper gives an overview of a research system for phoneme based, large vocabulary continuous speech recognition. The system to be described has been applied to the SPICOS task, the DARPA RM task and a 12000 word dictation task. Experimental results for these three tasks will be presented. Like many other systems, the recognition architecture is based on an integrated statistical approach. In this paper, we describe the characteristic features of the system as opposed to other systems: (1) The Viterbi criterion is consistently applied both in training and testing. (2) Continuous mixture densities are used without any tying or smoothing; this approach can be viewed as a sort of statistical template matching. (3) Time-synchronous beam search is used consistently throughout all tasks; extensions using a tree organization of the vocabulary and phoneme lookahead are presented so that a 12000 word task can be handled.

Synthesis for Off-line Testability - Hellebrand, Sybille; Juergensen, Arne; Wunderlich, Hans-Joachim

Chip Level Test Planning for Controlling the Tradeoff between Hardware Overhead and Test Time - Hellebrand, Sybille; Juergensen, Arne; Stroele, Albrecht; Wunderlich, Hans-Joachim

Approximate solution of a linear programming problem using a modified perceptron-algorithm. - Hüllermeier, Eyke (in Proceedings EUFIT-94 2nd European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Effiziente Testsatzkodierung für Prüfpfad-basierte Selbsttestarchitekturen - Venkataraman, Srikanth; Rajski, Janusz; Hellebrand, Sybille; Tarnick, Steffen
Keywords: WORKSHOP

Ein Verfahren zur testfreundlichen Steuerwerkssynthese - Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Synthesis for Testability - the ARCHIMEDES Approach - Hellebrand, Sybille; Paulo Teixeira, Joao; Wunderlich, Hans-Joachim
Keywords: WORKSHOP